Research on the impact of cross-border mergers and acquisitions on investment efficiency: evidence from Chinese listed companies - Kun Liu; Ying Zhu; Xiao Su; Lingchen Lu; Rui Fu (Humanities & Social Sciences Communications)
Abstract Compared to domestic mergers and acquisitions (M&As), the implementation of cross-border M&As by firms faces more uncertainties, and the risks of both M&A decisions and resource integration will increase. Using a sample of cross-border M&As from 2007 to 2020 in Chinese listed companies, this paper combines normative analysis and empirical tests to investigate the relationship between cross-border M&A and corporate investment efficiency. It further explores the regulatory mechanism of cross-border M&A on corporate investment efficiency. The results show that (1) cross-border M&As do not enhance the investment efficiency of Chinese enterprises; (2) cross-border M&As do not impact the investment efficiency of state-owned enterprises (SOEs) but exacerbate the inefficient investment of non-state-owned enterprises (non-SOEs), particularly in terms of over-investment. Heterogeneity tests reveal that the effect of cross-border M&As on investment efficiency is contingent upon various factors, including the type of property rights, financial constraints, and equity concentration of the merging companies. Furthermore, the level of economic development and governance in the host country and the degree of interconnectivity between the host and home nations also exert a notable influence.